Thyroid Autoimmunity in Female Infertility and Assisted Reproductive Technology Outcome - Bucci, Ines; Giuliani, Cesidio; Di Dalmazi, Giulia; Formoso, Gloria; Napolitano, Giorgio (Frontiers in Endocrinology, 2022)
The regulation of the female reproductive system is one of the most relevant actions of thyroid hormones. Adequate thyroid hormones production is essential for normal menstrual function and fertility as well as for the successful maintenance of pregnancy. The relationship between reproductive failure and thyroid disorders is particularly relevant and attracts attention worldwide. Thyroid autoimmunity (TAI), defined by the presence of circulating antithyroid antibodies (ATA) targeting thyroid peroxidase (TPOAb) and thyroglobulin (TgAb), is prevalent amongst women of reproductive age and is the most frequent cause of thyroid dysfunction. Several studies have looked at the association between TAI, thyroid function, and fertility as well as pregnancy outcome after spontaneous or assisted conception. Infertility, miscarriages, and fetal-maternal complications are described in overt autoimmune hypothyroidism. More debatable is the role of mild thyroid dysfunction, mainly subclinical hypothyroidism (SCH), and, mostly, of TAI per se, that is in absence of thyroid dysfunction in infertility and reproductive outcome. Indeed, TAI can affect fertility and pregnancy outcome by inducing hypothyroidism but also or by being pathogenic to the reproductive tissues but up to now a clear causation has not established. Assisted reproductive technology (ART) has become an integral element of care for infertility. Infertile patients with TAI undergoing ART are of particular interest since they carry a higher risk of developing hypothyroidism after the ovarian stimulation but whether TAI, when thyroid function is not affected, adversely affect ART outcome is still controversial. At the same conflicting results are reported on the role of levothyroxine (LT4) in improving fertility and the success of ART in euthyroid women with TAI. This review discusses the role of TAI, in the setting of euthyroidism, in infertility and ART outcome. Thyroid